From the Gracchi to Nero : a history of Rome from 133 B.C. to A.D. 68 - Scullard, Howard H. (Routledge classics, 2011)
From the Gracchi to Nero is an outstanding history of the Roman world from 133 BC to 68 AD. Fifty years since publication it is widely hailed as the classic survey of the period, going through many revised and updated editions until H.H. Scullard’s death. It explores the decline and fall of the Roman Republic and the establishment of the Pax Romana under the early Principate. In superbly clear style, Scullard brings vividly to life the Gracchi’s attempts at reform, the rise and fall of Marius and Sulla, Pompey and Caesar, society and culture in the late Roman Republic, the Augustan Principate, Tiberius and Gaius, Claudius and Nero, and economic and social life in the early Empire.